HD-PRO-TRIAD™ Validation: A Patient-reported Instrument for the Symptom Triad of Huntington's Disease. (14th April 2014) - Carlozzi, Noelle E.; Victorson, David; Sung, Victor; Beaumont, Jennifer L.; Cheng, Wendy; Gorin, Brian; Duh, Mei Sheng; Samuelson, David; Tulsky, David; Gutierrez, Sandra; Nowinski, Cindy J.; Mueller, Allison; et al.
Background: Few valid, disease-specific measures of health-related quality of life (HRQOL) capture the spectrum of symptoms associated with Huntington's disease (HD). The HD-PRO-TRIAD™ is a new, HD-specific, patient-reported outcome (PRO) instrument of the HD symptom triad (cognitive decline, emotional/behavioral dyscontrol, and motor dysfunction) designed for clinical research and practice. The objective was to validate the HD-PRO-TRIAD™ through a cross-sectional sample of individuals with HD and caregivers. Methods: Development of the HD-PRO-TRIAD™ has been described elsewhere. A total of 132 individuals with HD and 40 HD caregivers, comprising 29 dyads, participated in the cross-sectional psychometric validation of this instrument. Participants provided responses to the HD-PRO-TRIAD™ and other HRQOL and disease severity instruments (EuroQOL 5D, Short Form 12, Neuro-QOL Item Banks, PROMIS Global Health, and self-reported Unified Huntington's Disease Rating Scale Total Functional Capacity and Independence Scales). Internal consistency, construct validity, and patient–caregiver proxy consistency were evaluated. Results: Internal consistency of the three domains and overall HD-PRO-TRIAD™ instrument was supported by Cronbach's alpha values ≥0.94. Construct validity was supported by significant correlations between HD-PRO-TRIAD™ domain scores and other measures of the same domains (e.g., significant positive correlations between HD-PRO-TRIAD™ Anxiety with Neuro-QOL Anxiety), as well as slightly weaker but still strong correlations with other HRQOL instruments (e.g., HD-PRO-TRIAD™ Anxiety and UHDRS Independence; all p <0.01). Consistency between patient self-report and caregiver proxy report was supported by an intra-class correlation coefficient ≥0.92 for all three domains and the overall instrument. Discussion: These data indicate that HD-PRO-TRIAD™ is a reliable and valid HRQOL instrument that captures the typical triad of HD symptoms.